2005
DOI: 10.1124/dmd.104.002154
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of 1,5-Dicaffeoylquinic Acid in Rats, an in Vivo and in Vitro Study

Abstract: ABSTRACT:To explore the metabolism of 1,5-dicaffeoylquinic acid (1,5-DCQA) in rats, liquid chromatography-mass spectrometry in parallel to diode-array detection was used for the rapid detection/characterization of the metabolites formed in bile, urine, and plasma of rats following oral administration of 1,5-DCQA (160 mg/kg). The methylation and glucuronidation of 1,5-DCQA occurring in vitro using rat liver and small intestinal microsomes and cytosols were studied in comparison with those occurring in vivo, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 18 publications
0
21
2
Order By: Relevance
“…In this study, the major metabolites of demethoxycurcumin in urine were hexahydro-demethoxycurcumins (M-5 and M-6) and the 5-O-methyl-hexahydrodemethoxycurcumins (M-7 and M-8) together with traces of 5-dehydroxy-dihydro-demethoxycurcumins (M-9), whereas the major metabolites in feces were 5-dehydroxy-hexahydro-demethoxycurcumin (M-1 and M-2) and 5-dehydroxy-octahydro-demethoxycurcumin (M-3 and M-4). Combined with previous reports on the metabolism of curcuminoids (Holder et al, 1978;Wahlstrom et al, 1978;Ireson et al, 2001;Hoehle et al, 2006), it may be presumed that some demethoxycurcumin should initially undergo reduction to form dihydro-, tetrahydro-, hexahydro-(M-5 and M-6), and octahydro-demethoxycurcumin in a stepwise fashion (Ireson et al, 2002), followed by dehydroxylation (Feighner et al, 1980;Bokkenheuser et al, 1981;Kasahara et al, 1995) to form 5-dehydroxy-dihydro-(M-9), 5-dehydroxy-hexahydro-(M-1 and M-2), and 5-dehydroxy-octahydro-demethoxycurcumins (M-3 and M-4); on the other hand, some demethoxycurcumin may be initially methylated (Yang et al, 2005), followed by reduction to form 5-O-methyl-hexahydro-demethoxycurcumins (M-7 and M-8). Based on the metabolite profiles, the metabolic pathways of demethoxycurcumin in rats are proposed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the major metabolites of demethoxycurcumin in urine were hexahydro-demethoxycurcumins (M-5 and M-6) and the 5-O-methyl-hexahydrodemethoxycurcumins (M-7 and M-8) together with traces of 5-dehydroxy-dihydro-demethoxycurcumins (M-9), whereas the major metabolites in feces were 5-dehydroxy-hexahydro-demethoxycurcumin (M-1 and M-2) and 5-dehydroxy-octahydro-demethoxycurcumin (M-3 and M-4). Combined with previous reports on the metabolism of curcuminoids (Holder et al, 1978;Wahlstrom et al, 1978;Ireson et al, 2001;Hoehle et al, 2006), it may be presumed that some demethoxycurcumin should initially undergo reduction to form dihydro-, tetrahydro-, hexahydro-(M-5 and M-6), and octahydro-demethoxycurcumin in a stepwise fashion (Ireson et al, 2002), followed by dehydroxylation (Feighner et al, 1980;Bokkenheuser et al, 1981;Kasahara et al, 1995) to form 5-dehydroxy-dihydro-(M-9), 5-dehydroxy-hexahydro-(M-1 and M-2), and 5-dehydroxy-octahydro-demethoxycurcumins (M-3 and M-4); on the other hand, some demethoxycurcumin may be initially methylated (Yang et al, 2005), followed by reduction to form 5-O-methyl-hexahydro-demethoxycurcumins (M-7 and M-8). Based on the metabolite profiles, the metabolic pathways of demethoxycurcumin in rats are proposed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibition of human immunodeficiency virus-1 integrase and its replication [19][20][21], the antioxidant activities of caffeoylquinic acid derivatives [15,22] were also reported. However, no previous study has examined the activity of methyl 3,5-di-caffeoylquinate (3,5-diCQM) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the distribution, free concentration, and metabolism of various compounds can be affected as a result of binding to serum albumins in the blood stream. 18) From a review of the literatures, 14,[19][20][21] it was proposed that caffeic acid, tissular methylated metabolites (e.g. ferulic and isoferulic acids) and hippuric acid were some of the metabolites of CQAs (e.g.…”
mentioning
confidence: 99%
“…Most important, CQAs have been established as an important class of compounds with their potential effects of inhibiting human immunodeficiency virus (HIV)-1 integrase selectively and preventing HIV-1 replication in tissue culture at nontoxic concentrations. [12][13][14] Structure-activity relationship studies showed that their antioxidant, 5) antitumor, 6) hepatoprotective 7) and antimutagenicity 11) activities increased in proportion to the number of caffeoyl groups. Recently, it was also concluded that the radical scavenging activity of natural dicaffeoylquinic acids in the biological aqueous system might depend on the positions of caffeoyl ester groups.…”
mentioning
confidence: 99%